Emergency presentations in patients treated with immune checkpoint inhibitors. (May 2020) - Cooksley, Tim; Gupta, Avinash; Al-Sayed, Tamer; Lorigan, Paul
Abstract: Introduction: Immune-mediated toxicities are potentially fatal and can affect virtually any organ system. The prevalence of immune-mediated toxicity in patients being treated with immune checkpoint inhibitors (ICIs) is well described. However, the reasons for presentation and the prevalence of immune-mediated toxicity in acutely unwell patients being treated with ICIs is less well described. Materials and methods: A prospective analysis of all emergency presentations in patients being treated with ICIs was performed at a specialist oncology hospital in England from 20th May 2018 to 19th May 2019. The primary outcome measure was whether the emergency presentation related to an immune-mediated toxicity. Secondary outcome measures were length of stay associated with immune-mediated toxicities and 7- and 30-day mortalities related to these presentations. Results: During the study period, 300 patients on ICIs presented. The most common primary presenting complaints were dyspnoea 59 (19.7%), diarrhoea 47 (15.7%) and fever 37 (12.3%). Ninety-eight (32.7%) patients were diagnosed with an immune-mediated toxicity of which colitis 38 (38.8%), hepatitis 19 (19.4%) and pneumonitis 14 (14.3%) were the most common. The mean length of inpatient stay for those diagnosed with an immune-mediated presentation was 7.1 (0–45) days compared with 6.2 (0–44) days in those without. Seven patients died within 7 days of the emergency presentation, of whom 2 died from immune-mediated toxicity. Conclusions: One-third of cancer patients treated with ICIs admitted as an emergence had an immune-mediated toxicity and 2% died because of this. Acute care clinicians managing these patients need to be aware that immune-mediated toxicity is common in this patient population, but it can be challenging to differentiate these from other causes for emergency presentation. Highlights: One-third of emergency presentations in patients treated with checkpoint inhibitors are due to immune-mediated toxicity. Median duration of admission for patients treated for an immune-mediated toxicity is 4 days. Admitting under an acute oncology team with experience of IO toxicity is a model that allows optimisation of immediate management. There may be a role for an immune-oncology advisory team to optimise outcomes for patients. Management guidelines are empiric and more research is required, particularly at steroid sparing approaches.